IP Transcendence: Unifying IPv6 Over IPv4 Network - Sayalee Patil; Trupti Mate; Harshal Patil (International Journal of Electrical Power and Machine Systems, 2024)
Dynamic routing also called adaptive routing like traditional glass optical fiber, POF uses a polymethyl methacrylate (PMMA) core with a fluorinated polymer cladding, resulting in a larger core diameter that simplifies alignment and splicing. POF's adaptability is one of its main benefits. Because of their fragility and stiffness, ordinary glass fibers would not be practicable in certain situations where POF can be put. POF is a great option for intricate routing conditions since it can bend around corners and through small openings without breaking. POF's bandwidth capabilities have been greatly improved by recent developments in polymer technology, allowing it to sustain larger data rates. Recent advancements include the development of graded), where the core's refractive index gradually decreases from the center outward, minimizing modal dispersion and enhancing bandwidth. OF can now support data rates exceeding 10 Gbps over distances up to 100 meters, thanks to innovations in fiber structure and signal processing techniques. Improvements in polymer chemistry have significantly reduced attenuation and dispersion, making POF suitable for high-speed data transmission. Recent technical advancements in POF include the development of new polymer materials that reduce attenuation and enhance thermal stability, essential for maintaining performance under various environmental conditions. Advanced modulation techniques, such as discrete multitone (DMT) modulation and orthogonal frequency-division multiplexing (OFDM), are being explored to maximize data-carrying capacity. Future directions for POF technology.
Keywords: Enhance Data Transmission; Low Attenuation; Secure Data; Signal Integrity; optical fiber